Nature inspired catalysts: A review on electroactive microorganism-based catalysts for electrochemical applications - Bajracharya, Suman; Bian, Bin; Jimenez-Sandoval, Rodrigo; Matsakas, Leonidas; Katuri, Krishna P.; Saikaly, Pascal E. (Electrochimica acta, 2024)
The pursuit of efficient and sustainable electrochemical systems, that can generate green fuels and chemicals, stands as a primary contemporary challenge for sustaining a circular economy. As one of the main focuses in electrochemical systems, crafting robust electrocatalysts for various reactions, mostly based on expensive platinum group metals, has achieved plenty of attention in recent decades. To avoid the high cost and potential pollution associated with the synthesis of noble metal catalysts, nature-inspired catalysts, in particular catalysts based on electroactive microorganisms (EAM), serve as a valuable alternative for producing catalysts with intricate hierarchical structures and intrinsically scaling capability. This review aims to systematically detail the fundamental mechanisms of synthesis, potential applications, and future directions of EAM-based catalysts in electrochemical systems with emphasis on EAM-derived electrocatalysts and electrocatalysis. First, the synthesis methods, the mechanisms of synthesis, and the potential applications of EAM-derived electrocatalysts are discussed in detail. Second, the basics of microbial electrocatalysis, where EAM catalyzes various reactions at the electrodes of bioelectrochemical systems, are presented. The application of EAM catalysts in bioelectrochemical systems for organic matter degradation producing high current densities (> 2 A m−2), electrosynthesis of high-value chemicals from CO2, and the application of EAM-derived electrocatalysts for hydrogen/oxygen evolution reaction achieving comparable overpotentials to benchmark Pt/C and IrO2 catalyst (400 mV for HER and 370 mV for OER at 10 mA cm−2) are systematically summarized. Finally, challenges and new research directions are discussed, to shed light on the future implementation of EAM-based catalysts in sustainable electrochemical systems. [Display omitted]